The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s1516-14392002000300027
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical - Experimental Analysis of Cellular and Primary Dendritic Spacings during Unidirectional Solidification of Sn-Pb Alloys

Abstract: Structural parameters as grain size, dendritic and cellular spacings, segregated products, porosity and other phases are strongly influenced by the thermal behavior of the metal/mold system during solidification, imposing a close correlation between this and the resulting microstructure. Several unidirectional solidification studies with the objective of characterizing cellular and dendritic spacings have been developed in large scale involving solidification in steady-state heat flow. The main objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…Previous studies focusing on the growth of monophasic cells demonstrated that 0.55 and 1.1 exponents are effective in representing the variation of cell spacing against solidification cooling rate and solidification velocity, respectively [36,37]. The exponents derived based on the present results are quite similar to those reported in the literature.…”
Section: Resultssupporting
confidence: 82%
“…Previous studies focusing on the growth of monophasic cells demonstrated that 0.55 and 1.1 exponents are effective in representing the variation of cell spacing against solidification cooling rate and solidification velocity, respectively [36,37]. The exponents derived based on the present results are quite similar to those reported in the literature.…”
Section: Resultssupporting
confidence: 82%
“…It can be seen that, for the downward solidification, the same power law represents the variation of primary spacings with tip cooling rate for the 5 and 15wt.%Pb alloys. Figure 2a shows also a comparison with the experimental laws obtained from the vertical upward directional solidification of these two alloys 11 . As can be seen, for a same cooling rate, the primary spacing is reduced (about 2 to 3 times) for conditions of downward vertical solidification.…”
Section: Resultsmentioning
confidence: 94%
“…The experiments were performed with Sn-Pb alloys (5, 15 and 20wt.%Pb) with melt superheats of 7 °C above the liquidus temperature, and under a thermal contact condition at the metal/mold interface corresponding to the heat-extracting surface being polished. The employed thermophysical properties of these alloys are those reported in a previous article 11 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vários pesquisadores têm proposto correlações entre microestrutura de solidificação e parâmetros térmicos para ligas de vários sistemas binários Rocha, 2002;Bouchard-Kirkaldy, 1997;Çardili e Gündüz, 2000;Cruz, 2008;Santos, 2001] utilizando-se da determinação experimental dos espaçamentos celulares ou dendríticos e dos parâmetros térmicos de solidificação. Esses parâmetros são velocidades da isoterma liquidus, gradientes de temperatura e taxas de resfriamento.…”
Section: Correlação Dos Parâmetros Microestruturais Com As Variáveis Térmicasunclassified